KAJIAN BARU KRITIK HADITS JOSEPH SCHACT Studi Analisis “Teori Projecting Back” - Wely Dozan (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2018)
Studies of the early-era hadiths have gone through so long and strict phases of the scholars. Hadith which are authentic sources after the Al-Qur'an makes the scholars devote their attention to maintaining the validity and continuity of the hadith. One form of appreciation for the Hadith is the number of books which contain the Prophet's hadith as a medium to save the Prophet's qaul. in the course of the study of the hadith including the form of writing and gathering it was not as easy as it had in mind. Because of this difficulty and various challenges, a handful of scholars from the west emerged to enter and try to find loopholes to weaken the authenticity of a hadith. Among them there are those who devote almost a portion of their lives to studying and deepening the hadith. But the results of their study of hadith are not all purely for the development of science, especially in the discipline of ulum al-hadis. One contribution of their thinking in the study of hadith is the emergence of several theories which aim to sue and undermine the theory of established Muslim scholars. In this paper, we will explore further the thoughts of orientalists and western scholars, especially Joseph Schact, who want to try to undermine the authenticity of hadith through a theory known as "Projecting Back" as well as objections made by Muslims to the theory.